The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s11658-018-0073-5
|View full text |Cite
|
Sign up to set email alerts
|

The altered expression of perineuronal net elements during neural differentiation

Abstract: BackgroundPerineuronal nets (PNNs), which are localized around neurons during development, are specialized forms of neural extracellular matrix with neuroprotective and plasticity-regulating roles. Hyaluronan and proteoglycan link protein 1 (HAPLN1), tenascin-R (TNR) and aggrecan (ACAN) are key elements of PNNs. In diseases characterized by neuritogenesis defects, the expression of these proteins is known to be downregulated, suggesting that PNNs may have a role in neural differentiation.MethodsIn this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The most down-regulated AF proteins at term compared to midtrimester were HAPLN1, AFP, and LRP1B. HAPLN1 stabilizes the interactions between hyaluronic acid and proteoglycans, such as aggrecan and versican, in the extracellular matrix 79 81 , and the biological functions of HAPLN1 during fetal growth include chondrocyte differentiation and cartilage development 82 , heart development 83 , neural differentiation 84 , and neocortical folding 85 . LRP1B is a cell-surface receptor involved in receptor-mediated endocytosis 86 , expressed in the fetal brain 87 , where it may regulate apolipoprotein-mediated cholesterol uptake 88 .…”
Section: Discussionmentioning
confidence: 99%
“…The most down-regulated AF proteins at term compared to midtrimester were HAPLN1, AFP, and LRP1B. HAPLN1 stabilizes the interactions between hyaluronic acid and proteoglycans, such as aggrecan and versican, in the extracellular matrix 79 81 , and the biological functions of HAPLN1 during fetal growth include chondrocyte differentiation and cartilage development 82 , heart development 83 , neural differentiation 84 , and neocortical folding 85 . LRP1B is a cell-surface receptor involved in receptor-mediated endocytosis 86 , expressed in the fetal brain 87 , where it may regulate apolipoprotein-mediated cholesterol uptake 88 .…”
Section: Discussionmentioning
confidence: 99%
“…The glycoprotein tenascin-R is predominantly expressed by optic nerve oligodendrocytes and horizontal cells of the retina [28,38,39]. Tenascin-R can influence neurite outgrowth as well as neural and glial adhesion [35][36][37]. A domain-specific neuroprotective effect of tenascin-R has been described, presumably by regulation of microglia behavior [71].…”
Section: Unchanged Levels Of Tenascin-rmentioning
confidence: 99%
“…Tenascin-R can influence neurite outgrowth as well as neural and glial adhesion [35][36][37]. In the retina, tenascin-R is released by horizontal cells and accumulates in the plexiform layers.…”
Section: Introductionmentioning
confidence: 99%
“…37 Knockout mouse studies have also revealed a role in maintaining perineural nets (PNNs), a hyaluronan backbone meshlike network of proteins that surround neurons and regulate neuronal plasticity, 38 as well as neural differentiation and development. [39][40][41] Furthermore, PNNs are responsible for binding chemorepulsive molecules, such as Semaphorin3a, 42 and transcription factors, such as Otx2, that are exchanged between different neural cells to enhance cortical plasticity. 43 Hapln1a was recently shown to be necessary for ECM expansion in the developing zebrafish heart, and CRISPR-Cas9 hapln1a mutants show reduced atrial size and chamber ballooning.…”
Section: Introductionmentioning
confidence: 99%